Radiotracer studies of self diffusion of cd++ and cr+++ in agar gel - Gupta R.P.; Prasad G. (My University, 2025)
The selfdiffusion coefficients of Cd++ and GV+++ were studied at various temperatures and concentrations in agar gel media using tracer technique. The results indicate (i) an increase in the diffusion rate with the rise of temperature, (ii) a divergence between the theoretical and experimental values of diffusion coefficients. The experimental value, however, tends to approach the theoretical value at lower concentrations. © 1970, Walter de Gruyter. All rights reserved.